The Relationship of Salary And Annual Bonus To Employee Performance In Export Import Companies - Heriston Sianturi; Idah Yuniasih; Teni Agustina; Rooswhan Budhi Utomo; S Sriyanto; Arman Syah Putra (IJISTECH (International Journal of Information System and Technology), 2022)
The background of scientific writing is how to find out the relationship between annual bonus salaries and employee performance do these three variables have a significant relationship or not, therefore with this research it will be known whether the variables can be related to the company even better. The method in this study uses a quantitative method by conducting a survey of 100 employees at an import-export company and conducting a literature review study in order to find research problems that can be raised with very high novelty carried out by researchers. The problem raised in this study is there is a relationship between salary and employee performance then is there a relationship between annual bonuses and employee performance with the 2 hypotheses, it will be sought to find out whether the two variables and other variables are related to each other significantly. This study produces data, namely, there is a very significant relationship between salary and employee performance which has a significant value of 0.003 and there is a significant relationship between annual bonuses and employee performance which has a significant value of 0.002 with this value, the independent and dependent variables have a significant relationship very significant.